Atmospheric CO2 and Climate: Taylor Dome Ice Core, Antarctica - Brook, Edward J; Ahn, Jinho (IEDA: US Antarctic Program Data Center, 2007)
Abstract: Using new and existing ice core CO2 data from 65 - 30 ka BP a new chronology for Taylor Dome ice core CO2 is established and synchronized with Greenland ice core records to study how high latitude climate change and the carbon cycle were linked during the last glacial period. The new data and chronology should provide a better target for models attempting to explain CO2 variability and abrupt climate change.